Whole grain in manufactured foods: Current use, challenges and the way forward. Issue 8 (24th May 2017) - Schaffer-Lequart, Christelle; Lehmann, Undine; Ross, Alastair B.; Roger, Olivier; Eldridge, Alison L.; Ananta, Edwin; Bietry, Marie-France; King, Luis R.; Moroni, Alice V.; Srichuwong, Sathaporn; Wavreille, Anne-Sophie; Redgwell, Robert; et al.
ABSTRACT: Some countries now incorporate recommendations for increased consumption of whole grain (WG) into local dietary guidelines. Cereal and pseudo-cereal grains are good sources of complex carbohydrates, dietary fiber, proteins, phytochemicals, vitamins and minerals. However, research shows that the large majority of consumers are still falling short of WG consumption goals. To address this, we are actively involved in research to help increase the WG content of processed foods without compromising on taste and texture. In order to ensure consumer trust, the advancement of process technologies in incorporating WG to produce tasty food has to go hand in hand with well designed clinical trials that confirm the health benefits resulting from diets rich in WG.